Answer:
(2,1) is the only solution to the linear equation
Explanation:
to solve, just plug in the values given into the orignal expression. remember, the answer on the left has to be equal to the answer on the right.
(2,1)
4(2) + 3(1) = 11 --> 8 + 3 = 11 --> 11 = 11 (2,1) is a solution to the linear equation
(6,0)
4(6) + 3(0) = 11 --> 24 + 0 = 11 --> 24 ≠ 11 (6,0) is not a solution to the linear equation
(0,1)
4(0) + 3(1) = 11 --> 0 + 3 = 11 --> 3 ≠ 11 (0,1) is not a solution to the linear equation